Tomate salada: Uma alternativa como fonte de antioxidante para uso tópico - Cefali, Letícia C. [UNESP]; Rinaldo, Daniel [UNESP]; Barbosa, Vanessa De F. [UNESP]; Salgado, Hérida R. N. [UNESP]; Vilegas, Wagner [UNESP]; Oliveira, Olga M.M. De F. [UNESP]; Isaac, Vera L.B. [UNESP] (My University, 2009)
Tomato is the principal source of lycopene, a carotenoid with high antioxidant activity which can be used topically as a phytocosmetic to combat skin aging. The aim of this study was to get a lycopene-rich extract from salad tomato pulp. The extract was analyzed using UV/vis spectroscopy, thin layer chromatography and high performance liquid chromatography. Oxidant activity was analyzed using the free radical DPPH method. The presence of lycopene in the salad tomato was confirmed. It was present in the apolar fraction rich in carotenoids, which was 96.70% lycopene. In the evaluation of the antioxidant activity, using the radical DPPH, the extract showed activity (IC50 = 0,311 mg/mL). We conclude that the salad tomato can be used as a source of antioxidants for topic use.
Tomato salad: An alternative as antioxidant source for topic use
Keywords: Lycopene; Phytocosmetic; Tomato